2011
DOI: 10.1111/j.1532-5415.2010.03271.x
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Vaccination in Young Children Reduces Influenza-Associated Hospitalizations in Older Adults, 2002-2006

Abstract: OBJECTIVES To assess how influenza vaccination coverage in children is related to pneumonia and influenza (P&I) in US seniors and if these associations are modified by sociodemographic factors. DESIGN We abstracted approximately 5 million hospitalization records from the Centers for Medicare and Medicaid Services for four influenza years, 2002–2006. We estimated a single year age distribution of rates of P&I hospitalization by state for each influenza season and observed an exponential acceleration in the P&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…In the USA, influenza vaccinations have been reported to improve school attendance rates [21], and vaccinating children for influenza has been found to induce herd immunity in elderly populations [22]. Our findings support a possible sizable effect of schoolchildren (elementary to junior high school) on the spread of infection to the whole population.…”
Section: Discussionsupporting
confidence: 77%
“…In the USA, influenza vaccinations have been reported to improve school attendance rates [21], and vaccinating children for influenza has been found to induce herd immunity in elderly populations [22]. Our findings support a possible sizable effect of schoolchildren (elementary to junior high school) on the spread of infection to the whole population.…”
Section: Discussionsupporting
confidence: 77%
“…35 years and pneumonia and influenza hospitalization rates in those age 65 years, although vaccine uptake was low in the elderly [37][38][39]. Similar benefits have been reported in modelling studies in the UK and Germany [40,41].…”
Section: Strategies For Improving Vaccination Effectiveness In the Elsupporting
confidence: 60%
“…As a testament to the significant toll posed by influenza on public health and healthcare systems, the US Centers for Disease Control and Prevention (CDC) estimated that from 2010 to 2015, influenza infections resulted in 9.23-35.6 million illnesses and 139,000-707,000 hospitalizations annually in the US alone [9]. It has been suggested that children are likely the primary transmitters of influenza [10]. Lethal influenza infections are primarily associated with high risk populations, including infants (< 1 year), the elderly (> 65 years), and individuals with pre-existing comorbidities, including chronic respiratory abnormalities, cardiac disease, immunodeficiency, and pregnancy [11,12].…”
Section: General Influenza Epidemiologymentioning
confidence: 99%